The LARK protein is involved in antiviral and antibacterial responses in shrimp by regulating humoral immunity. (January 2021) - Yang, Linwei; Wang, Zi-ang; Zuo, Hongliang; Geng, Ran; Guo, Zhixun; Niu, Shengwen; Weng, Shaoping; He, Jianguo; Xu, Xiaopeng
Abstract: The LARK proteins containing a C2HC-type zinc finger motif and two RNA recognition motifs are conserved across vertebrates and invertebrates. Previous studies have suggested that invertebrate LARKs and their mammalian counterparts, the RBM4 proteins, regulate gene expression by affecting RNA stability and post-transcriptional processing, participating in multiple life processes. In the current study, the LARK gene from Pacific white shrimp Litopenaeus vannamei was identified and functionally explored in the context of immunity. The LARK protein was mainly present in the nucleus of its expression vector-transfected S2 cells, and the LARK mRNA was detectable in all the tested shrimp tissues. Expression of LARK in gill was up-regulated by immune stimulation with various pathogens. In vivo experiments demonstrated that LARK played positive roles in both antiviral and antibacterial responses and silencing of LARK could make shrimp more susceptible to infection with Vibrio parahaemolyticus and white spot syndrome virus (WSSV). Although silencing of LARK did not affect the phagocytic activity of hemocytes, it regulated expression of many components of the NF-κB and JAK-STAT pathways and a series of immune function proteins. These suggested that LARK could be mainly involved in regulation of humoral immunity. The current study could help reveal the roles of LARK/RBM4 in immunity and further explore the regulatory mechanisms of shrimp immunity. Highlights: LARK enhanced antiviral and antibacterial responses in shrimp. LARK regulated expression of a series of immune related genes in shrimp. LARK did not affect the phagocytosis of shrimp hemocytes.